Qualidade de vida no trabalho: um estudo com servidores públicos municipais - Marsaro, Alessandra Back de Rezende (2025)
The objective of this study is analyzing the perception of municipal public employee of the Basic Health Units (BHU) and administrative officers of the Municipal Secretariats, both in the Municipality of Serranópolis do Iguaçu - Paraná, in regard to the quality of life at work (QWL). For this purpose, exploratory applied quantitative research was carried out in the form of a case study, with the participation of 124 municipal public officials from the sectors of interest. In the interest of identifying the perception of the servants in relation to their QWL, it was chosen measuring the general perception and in the physical/health, psychological, personal and professional domains. For this reason, the QWLQ-78 questionnaire was used as the base instrument, since it is a closed structured questionnaire using the five-point Likert scale. However, due the fact that it is a small municipal public environment and considering the characteristics of the research and analysis environment of the original questionnaire, it was decided to adapt the instrument, considering the original complexity could compromise the application and data collection. The instrument was validated and subsequently applied. The results obtained in the specific questionnaire were analyzed directly – through the QWL results – and also statistically using the Cronbach's alpha, Spearman's correlation, and Mann-Whitney U techniques. The results indicate a neutral/satisfactory perception of QWL in general (3.59) with good satisfaction (4.0) from all subgroups in the personal domain. In the personal and psychological domains, all subgroups can be considered homogeneous among themselves, but discrepancies were measured between the UBS and the administrative subgroup in the professional and physical domains, with the perception of the UBS being less satisfactory than that of the administrative subgroup.